Dynamic analysis and motion measurement of ski turns using inertial and force sensors - Hirose, K.; Doki, H.; Kondo, A. (Procedia Engineering, 2013)
This paper proposes the dynamic motion analysis method of ski turns using inertial and force sensors. The motion analysis of ski turns in gliding on an actual field is important to resolve the mechanism of ski turns. However, it is difficult to measure physical exertion due to the severe experimental surrounding such as the outside snow conditions and the weather on the mountain. Therefore, few studies have analyzed ski turns quantitatively. The control force of skier gliding on the actual snow field must be clarified to resolve the mechanism of ski turns. In the previous studies, we developed the 3D posture estimation method of skier gliding at high speed. This method can estimate the Roll- Pitch-Yaw angles in local coordinate by the information of inertial sensors using the Unscented Kalman filter. The control force of skier (joint torque) can be calculated by combining this method and the measurement of reaction force from snow surface. We conducted the experiment of skier gliding on the actual snow field. The inertial sensors were attached to the body segments (upper body, lumber, femur, and lower thigh) of skier and ski boots, and the 6- axis force sensors were installed between boots and skis. The inertial sensors measure angular velocity and acceleration of body segments, and the force sensors measure the reaction force from snow surface. The joint torque (lumber spine, hip, knee and ankle) of skier is calculated by applying the measurement information to the Newton- Euler method. The analysis results using joint torque indicates the control force of skier gliding on the actual snow field. Therefore, the analysis method and results can be used to evaluate the skill of turns and to resolve the mechanism of ski turns.